2023
DOI: 10.3390/ani13152404
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence to Predict the BRAF V595E Mutation in Canine Urinary Bladder Urothelial Carcinomas

Leonore Küchler,
Caroline Posthaus,
Kathrin Jäger
et al.

Abstract: In dogs, the BRAF mutation (V595E) is common in bladder and prostate cancer and represents a specific diagnostic marker. Recent advantages in artificial intelligence (AI) offer new opportunities in the field of tumour marker detection. While AI histology studies have been conducted in humans to detect BRAF mutation in cancer, comparable studies in animals are lacking. In this study, we used commercially available AI histology software to predict BRAF mutation in whole slide images (WSI) of bladder urothelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…In the present study, 72/122 (59%) UC and 13/21 (65%) PC were BRAF V595E mutated. This is in accordance with the prevalence of the mutation reported in the literature using PCR, 5–7,9,20 despite our limitation of a small sample size of PC cases. In the dog, BRAF V595E is considered a diagnostic marker for UC and PC 5,20 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, 72/122 (59%) UC and 13/21 (65%) PC were BRAF V595E mutated. This is in accordance with the prevalence of the mutation reported in the literature using PCR, 5–7,9,20 despite our limitation of a small sample size of PC cases. In the dog, BRAF V595E is considered a diagnostic marker for UC and PC 5,20 .…”
Section: Discussionsupporting
confidence: 92%
“…For instance, in thyroid cancer, it is strongly linked with either the papillary or anaplastic morphology, 34 and in melanomas, it is associated with pigmentation, scatter of intraepidermal melanocytes and solar elastosis 35 . Our recent study using artificial intelligence to analyse canine urinary bladder tumours revealed that BRAF mutations in these cases frequently corresponded with papillary growth, smooth and pushing rather than invasive tumour fronts 7 . The present investigations support a parallel between the morphological implications of BRAF mutations in both human and canine cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In veterinary oncology, investigations of deep learning-based tumour histology are starting to be performed on canine tumours, wherein artificial intelligence (AI)-based methods are using digitized whole-slide images (WSIs) to make pathological diagnoses, such as diagnosing canine skin tumours (of seven different types) [ 144 , 145 ] and canine osteosarcoma (where the AI program was able to identify specific histologic subtypes that may have prognostic value) [ 146 ]. However, to date, there has only been one genotype–phenotype correlation study in canines; it was recently shown that deep learning using a commercial AI histology software could detect the BRAF p.V595E mutation on HE-stained canine bladder cancer tissue sections ( Figure 9 ), with a sensitivity of 89% [ 147 ].…”
Section: Emerging Fields For Genetic Investigations Of Canine Tumoursmentioning
confidence: 99%
“…may have prognostic value) [146]. However, to date, there has only been one genotypephenotype correlation study in canines; it was recently shown that deep learning using a commercial AI histology software could detect the BRAF p.V595E mutation on HE-stained canine bladder cancer tissue sections (Figure 9), with a sensitivity of 89% [147].…”
Section: Prediction Of Genetic Alterations From Histology Slidesmentioning
confidence: 99%